Wisconsin's Water : Establishing an Environmental Trace Metal Baseline for Responsible and Reasonable Regulation - Lindquist, Derek; Wiest, Adam; Mahoney, J. Brian; Hackenmueller, Melissa; Mueller, Carly (My University, 2018)
The primary objective of this investigation is to conduct a comprehensive analysis of surface water and groundwater chemistry throughout western Wisconsin. This analysis will establish an environmental baseline that will document natural background variations in dissolved metal content in surface water and groundwater throughout the region. These data are essential for establishing a baseline that may be used in developing reasonable and responsible environmental regulations.
Color poster with text, graphs, maps, and images.
Keywords: Environmental issues; Groundwater--Wisconsin; Posters; Sand mining